2000
DOI: 10.1109/60.866993
|View full text |Cite
|
Sign up to set email alerts
|

A method for magnetizing curve identification in rotor flux oriented induction machines

Abstract: Operation of an indirect rotor flux oriented induction machine in the field weakening region is usually realized by varying the rotor flux reference in inverse proportion to the speed of rotation. In order to provide the correct stator d-axis current reference at all speeds, it is necessary to incorporate the inverse magnetizing curve of the machine in the controller. The paper proposes an experimental method for identifying the inverse magnetizing curve, specifically developed for the type of vector controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(34 citation statements)
references
References 15 publications
0
31
0
3
Order By: Relevance
“…5...8); -the difference between the torques measured in both situations becomes more significant when the rotor mechanical speed is increased (Figs. 6 and 7); -a small difference (lower than 1%) can be noticed between the torque estimated with (13) and the reference value.…”
Section: The Experimental Tests With the Dspace Platformmentioning
confidence: 88%
See 1 more Smart Citation
“…5...8); -the difference between the torques measured in both situations becomes more significant when the rotor mechanical speed is increased (Figs. 6 and 7); -a small difference (lower than 1%) can be noticed between the torque estimated with (13) and the reference value.…”
Section: The Experimental Tests With the Dspace Platformmentioning
confidence: 88%
“…The scope of this technique is to improve the drive system's performances in this range of speeds for the control of torque. Additionally, in the flux weakening region, the performed control algorithm was modified such as to take into consideration the variation of inductance of magnetizing [13] and the adaptive field weakening [14]. The blocks 1 and 2 from …”
Section: Description Of the Indirect Vector Control Algorithm Conmentioning
confidence: 99%
“…The main drawback of this method is that it is not suitable for the self-commissioning scheme. The method presented in [9], which deals with the parameter identification of the analytical inverse magnetization curve implemented in the control system, requires that the machine is not coupled to the load and that the voltage measuring equipment is available. A newer paper dealing with the self-commissioning at standstill does not deal with the magnetization curve at all [10].…”
Section: Introductionmentioning
confidence: 99%
“…There were another group of researches being emphasized on the consideration of magnetic saturation effect and its compensation control. In the research conducted in [7], an inverse magnetizing curve is identified and applied for performing the field-orientation control. As the control scheme developed in [8], a programmed magnetizing current considering the saturation effect and current and voltage limits over wide field-weakening range is employed to obtain maximum torque.…”
Section: Introductionmentioning
confidence: 99%